The Role of Artificial Intelligence in Enhancing Learning Motivation through Self and Immediate Feedback - Zahraa Aldahlaki (Indonesian Journal Publisher, 2026)
This study is what you need to understand the power of AI-based rapid feedback in motivating university students to learn. In a quasi-experimental study we compare two groups; one group that receive feedback through AI and the other group that uses traditional methods. The AI group should have more motivation especially when they grow more independent, capable and involved. The findings will aid educators and technology companies as they seek to enhance AI tools for blended learning, and the focus will be on Arab colleges.